Simulating the Impact of Long-Range-Transported Asian Mineral Dust on the Formation of Sulfate and Nitrate during the KORUS-AQ Campaign - Yu, Zechen; Jang, Myoseon; Kim, Soontae; Bae, Changhan; Koo, Bonyoung; Beardsley, Ross; Park, Jinsoo; Chang, Lim Seok; Lee, Hee Choon; Lim, Yun Kyu; Cho, Jeong Hoon (ACS Earth and Space Chemistry, 2020)
The atmospheric mineral aerosol reaction (AMAR) model, which was developed to simulate dust-driven heterogeneous chemistry of SO2 and NOx, was combined with the comprehensive air quality model with extensions (CAMx). The resulting model was then applied to simulate the influence of the long-range-transported dust particles on the formation of sulfate and nitrate during the Korean-United States Air Quality (KORUS-AQ) campaign from May 19 to 30, 2016. In the mechanisms, dust particles promoted the oxidation of SO2 and NOx through heterogeneous photocatalytic reactions and autoxidation. The predicted concentrations of sulfate, nitrate, and ammonium ions were compared with ground-based observations obtained at a monitoring site in Olympic Park, Seoul, Korea. The predicted sulfate increased by 29% in the high dust period of this campaign, while the sulfate produced via nondust aqueous reactions decreased by 66%. The model captured the impact of dust on the sulfate formation in that particulate sulfate increased with increasing dust loads. The model also predicted the formation of a large quantity of particulate nitrate during the cold and wet periods in the presence of abundant ammonia in East Asia. The trajectory simulations showed that dust particles were rapidly buffered by sulfate when dust parcels passed urban and industrial areas in Asia and then heavily coated with sulfate and nitrate during long-range transport. The KORUS-AQ campaign was conducted after passing the dust season (i.e., springtime), although dust concentrations were still higher than those in ordinary seasons. Thus, the impact of dust particles on the formation of sulfate and nitrate will be more significant during dust events.
Keywords: CAMx; heterogeneous chemistry; KORUS-AQ; mineral dust; nitrate; sulfate